Nandrolone administration with or without strenuous exercise promotes overexpression of nephrin and podocin genes and induces structural and functional alterations in the kidneys of rats. (5th January 2018) - Tofighi, Asghar; Ahmadi, Shima; Seyyedi, Seyyedeh Masoumeh; Shirpoor, Alireza; Kheradmand, Fatemeh; Gharalari, Farzaneh Hosseini
Highlights: Nandrolone treatment with or without training increased 8-OHdG as a DNA damage marker. Nandrolone treatment with or without training increased nephrin and podocin gene expression. Nandrolone treatment with or without training led to kidney function alteration. Abstract: Among the various adverse effects of nandrolone administration with or without strenuous exercise, kidney abnormalities, where there are associations between nandrolone decanoate consumption, have not been well defined yet. The aim of this study was to investigate the effect of nandrolone decanoate intake with or without strenuous exercise on nephrin and podocin gene expressions, cystatin C, oxidative DNA damage, and histological changes in the kidneys of rats. Thirty-two male wistar rats were assigned into four groups, namely control, nandrolone, nandrolone with strenuous exercise, and strenuous exercise groups. After six weeks of treatment, the results revealed a significant increase in the nephrin and podocin gene expression, plasma cystatin C, and the amount of 8-OHdG in the kidney tissue; as well as a decrease in creatinine clearance in nandrolone and nandrolone with strenuous exercise groups compared to the control group. Moreover, compared to the control group, the nandrolone and the nandrolone with strenuous exercise groups, showed histological changes such as fibrosis and kidney tissue cells proliferation. These findings indicate that nandrolone induces kidney abnormalities, which may in part be associated with overexpression of nephrin and podocin genes mediated by oxidative stress, which was manifested in increased 8-OHdG in kidney tissue.